Malleable Mitochondrion of Trypanosoma brucei - Verner, Zdeněk; Basu, Somsuvro; Benz, Corinna; Dixit, Sameer; Dobáková, Eva; Faktorová, Drahomíra; Hashimi, Mir Mohamod Hassan; Horáková, Eva; Huang, Zhenqiu; Paris, Zdeněk; Peña-Diaz, Priscila; Ridlon, Lucie; et al. (Elsevier Sc., 2015)
The importance of mitochondria for a typical aerobic eukaryotic cell is undeniable, as the list of necessary mitochondrial processes is steadily growing. Here, we summarize the current knowledge of mitochondrial biology of an early-branching parasitic protist, Trypanosoma brucei, a causative agent of serious human and cattle diseases. We present a comprehensive survey of its mitochondrial pathways including kinetoplast DNA replication and maintenance, gene expression, protein and metabolite import, major metabolic pathways, Fe-S cluster synthesis, ion homeostasis, organellar dynamics, and other processes. As we describe in this chapter, the single mitochondrion of T. brucei is everything but simple and as such rivals mitochondria of multicellular organisms
Keywords: kDNA; Kinetoplast; Metabolism; Mitochondrial transport; Mitochondrion; RNA import; T. brucei; Trypanosome